Analgesic effects of intraarticular and regional intravenous morphine after arthroscopic knee surgery - (:unkn) unknown (MONDUZZI EDITORE, 1996)
In this study, it was aimed to compare the efficacy of intraarticular and regional intravenous morphine chloride after arthroscopic knee surgery. The effect of morphine hydrochloride 5mg in 20ml volume administered either through 22G intravenous catheter applied at the extremity to be operated or through the arthroscope into the synovial cavity at the end of the surgery was studied in 20 patients. The postoperative pain was assessed with visual analogue scale at 1., 2., 6., 12., and 24. hours and analgesic requirements, sedation scores and complications were recorded. The mean pain scores of Group I(regional intravenous) were not significantly different from Group II( intraarticular )at any time. It was concluded that morphine hydrochloride 5mg in 20ml volume given either by intraarticular or regional intravenous routes provides effective postoperative analgesia after arthroscopic knee surgery.